Mesodermal cell fate decisions in Drosophila are under the control of the lineage genes numb, Notch and sanpodo. - Park, M.; Yaich, L.E.; Bodmer, R. (Mechanisms of Development, 1998)
In Drosophila, much has been learned about the specification of neuronal cell fates but little is known about the lineage of mesodermal cells with different developmental fates. Initially in development, individual mesodermal precursor cells are singled out to become the founder cells for specific muscles. The selection of muscle founder cells is thought to employ a Notch-mediated process of lateral inhibition, similar to what is observed for the specification of neural precursors. These muscle founder cells then seem to fuse with the surrounding, uncommitted myocytes inducing the formation of muscle fiber syncytia. In contrast, the differentiated progeny of neural precursor cells are usually the result of a fixed pattern of asymmetric cell divisions which are directed, in part, by interactions between numb, a localized intracellular-receptor protein, sanpodo (spdo), a potential tropomodulin homolog, and Notch, a transmembrane receptor protein. Here, we have investigated the role of these neural lineage genes in the cell fate specification of muscle and heart precursors. In particular, we have focused on a progenitor cell that is likely to produce a mixed lineage, generating both a pericardial heart cell and a somatic muscle founder cell. We show that the asymmetric segregation of Numb into one of these daughter cells antagonizes the function of Notch and spdo by preventing the presumptive muscle founder from assuming the same fate as its cardiac sibling. Our results suggest that asymmetric cell divisions, in addition to the previously-documented inductive mechanisms, play a major role in cardiac and somatic muscle patterning and that additionally the cytoskeleton may have a role in the asymmetrical localization of cell fate determinants.